Peran Sumber Daya Manusia Dalam Perencanaan dan Pengembangan Karir Pada Organisasi Nirlaba : Tinjauan Pustaka - Risa Ratna Gumilang (Coopetition : Jurnal Ilmiah Manajemen, 2022)
Literature review aims to explore and evaluate previous research that has focused on the role of Human Resources in planning and career development in nonprofit organization. Several frameworks are explored and discussed. In this article, there is some evidence that shows that non-profit organizations have planning and career development that aims to achieve organizational goals, especially in the social aspect. This article has been reviewed based on research findings, methodology, country studied, and year of publication. The largest contribution of these 40 main research articles came from the United States (45%) and the highest published by researchers in 2017 (27.5%) with empirical study research methods (42%), The largest source of articles was obtained from the Nonprofit and Voluntary Sector Quarterly (22.5%). This article describes descriptive analysis and qualitative thematic analysis to describe the analysis of the role of Human Resources in career planning and development in non-profit organizations in order to increase workforce loyalty and minimize turnover.